VD_FINDINFO Jug / 2013 / 82 vom 20. November 2012 - VD Tribunal cantonal (2012)
MEURTRE, TENTATIVEDROIT PÉNAL, SURSIS À L'EXÉCUTION DE LA PEINE | 111 CP, 19 al. 2 CP, 22 ad 111 CP, 40 CP, 43 CP, 47 CP, 51 CP